200k views
4 votes
DUE RIGHT NOWWWW!!! PLEASE HELP!!!!

DUE RIGHT NOWWWW!!! PLEASE HELP!!!!-example-1
User Fjxx
by
6.6k points

1 Answer

3 votes

Answer:

Infinite Solutions

Explanation:


(2x + 6)/(4) = (1)/(2) x + (3)/(2)

Get rid of the denominators by multiplying all whole equation by 4.


( (2x + 6)/( 4) )4 = ( (x)/(2) )4 +( (3)/(2) )4 \\ 2x + 6 = 2x + 6

The interesting part is here. Both sides are same, meaning that if we continue to solve for the equation.


2x + 6 = 2x + 6 \\ 2x - 2x = 6 - 6 \\ 0 = 0

The equation is indeed true. Meaning that both graphs are the same and intercept both each others infinitely.

Therefore the answer is Infinite solution.

User Pedro Polonia
by
6.4k points